2014
DOI: 10.1016/j.biortech.2014.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of complex effluent treatability in different bench scale microbial electrolysis cells

Abstract: A range of wastewaters and substrates were examined using mini microbial electrolysis cells (mini MECs) to see if they could be used to predict the performance of larger-scale cube MECs. COD removals and coulombic efficiencies corresponded well between the two reactor designs for individual samples, with 66-92% of COD removed for all samples. Current generation was consistent between the reactor types for acetate (AC) and fermentation effluent (FE) samples, but less consistent with industrial (IW) and domestic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 25 publications
0
6
1
Order By: Relevance
“…Some researchers even note that ARB is capable to directly oxidize cathodic H 2 for electron production (H 2 → 2H + + 2e -→ current) [30]. The hydrogen recycling phenomenon was also confirmed by other researchers in literature, such as Ullery and Logan [2], who, in comprising complex effluent treatability in mini and larger-scale cube MECs, documented that the cells both gave γ CE values greater than 100%, and Montpart et al [30], who, in a methanol-driven MEC, reported a γ CAT even reaching up to 296%. As a result of the occurrence of hydrogen recycling effect, net hydrogen output was reduced.…”
Section: Hydrogen and Energy Efficiencymentioning
confidence: 54%
See 1 more Smart Citation
“…Some researchers even note that ARB is capable to directly oxidize cathodic H 2 for electron production (H 2 → 2H + + 2e -→ current) [30]. The hydrogen recycling phenomenon was also confirmed by other researchers in literature, such as Ullery and Logan [2], who, in comprising complex effluent treatability in mini and larger-scale cube MECs, documented that the cells both gave γ CE values greater than 100%, and Montpart et al [30], who, in a methanol-driven MEC, reported a γ CAT even reaching up to 296%. As a result of the occurrence of hydrogen recycling effect, net hydrogen output was reduced.…”
Section: Hydrogen and Energy Efficiencymentioning
confidence: 54%
“…Exploring sustainable energy alternatives to fossil fuels is becoming of great importance to alleviate the energy shortage. One of the potential alternative renewable energy resources that are currently under-utilized is dissolved organic matters present in wastewater streams [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ullery and Logan (Ullery & Logan, 2014) examined the impact of anode acclimation strategy (using different substrate: acetate or domestic wastewater) on the treatment efficiency of cellulose fermentation effluent. It was found that the pre-acclimation strategy of using domestic wastewater or acetate in MECs had no significant difference in COD treatment, current generation, and coulombic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Higher hydrogen gas production rates could possibly be obtained by using higher MREC influent COD concentrations, as this should increase COD removal rate and stabilize anode potentials. The fermentation wastewater examined here was diluted to a concentration to be similar to those previously used in MECs (Lalaurette et al, 2009;Nam et al, 2012;Nam et al, , 2014Ullery and Logan, 2014), so the use of higher influent COD concentrations could easily be achieved. The effect of organic loading on the MREC performance, in terms of anode potentials and hydrogen gas production rates, should therefore be examined in future studies.…”
Section: Current Generation and Hydrogen Production Using Fermentatiomentioning
confidence: 99%
“…The volume of hydrogen produced was determined using a method based on gas concentrations relative to initial nitrogen gas concentration in the gas collection bag compared to concentrations after an addition of 10 mL of nitrogen was added to the gas bag, as previously described (Ambler and Logan, 2011;Ullery and Logan, 2014). Hydrogen production rate (Q, L H 2 /L reactor /d) was normalized to the reactor volume of the anode and cathode chambers.…”
Section: Experimental Measurements and Calculationsmentioning
confidence: 99%